Response to commentaries to Luck et al. (2021). Progress toward resolving the attentional capture debate. Issue 9 (21st October 2021) - Theeuwes, Jan
ABSTRACT: In a review paper, Luck et al. [(2021). Progress toward resolving the attentional capture debate. Visual Cognition, 29(1), 1–21. https://doi.org/10.1080/13506285.2020.1848949] discussed multiple perspectives on the attentional capture debate. In response to this review paper, several commentaries were written. Here, I respond to these commentaries and discuss those issues that seem to be the most pressing in the discussion on whether progress is made. I particularly focus on issues that are relevant from my point of view. I have organized the reply to the commentators into separate sections and addressed the issues that were commonly raised.